PENGEMBANGAN MEDIA EVALUASI INTERAKTIF BERBASIS GAME BOOKWIDGETS DALAM PEMBELAJARAN PAI DAN BUDI PEKERTI KELAS VIII SMPN 2 BANGILAN TUBAN - Sabela, Sevia Nur; Muthi'udin, Ahmad; Nisa, Ida Fauziatin (TADBIR : Journal of Islamic Education Management, 2025)
In the digital era and the advancement of Industry 5.0 technology, learning is required to be more innovative in order to increase student engagement, especially in assessment activities that tend to be conventional and less appealing. This study aims to develop an interactive evaluation media based on BookWidgets games for Islamic Religious Education and Character Education for grade VIII students at SMPN 2 Bangilan Tuban. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product is an interactive evaluation in the form of a crossword puzzle that can be accessed online. Validation by material experts indicated a feasibility level of 95%, media experts 83.96%, teacher responses 97.5%, and student responses 87.5%. The results show that this media is highly feasible and effective in increasing students' motivation and understanding.